Prevalence and pattern of hearing loss among meningitis survivors in the Pacific Islands: a prospective, observational study protocol - Annette Kaspar; Sione Pifeleti; Carlie Driscoll (Inishmore Laser Scientific Publishing Ltd, 2021)
# Background Permanent hearing loss is the most common neurological sequelae among meningitis survivors in low- and middle-income countries. It is preventable through the availability and optimal population coverage of immunization programs. The most recent Global Burden of Disease Project reported that mortality and morbidity rates associated with meningitis are in decline in the Pacific Islands. While the report is encouraging, clinical and rehabilitation services for meningitis survivors remain important for regions where immunization delivery is unable to reach optimal levels. The aim of the proposed study is to assess the prevalence and pattern of hearing impairment among meningitis survivors in Samoa, a Polynesian nation of the Pacific Islands. # Methods and analysis This will be a prospective observational study design. All patients admitted to Tupua Tamasese Meaole Hospital with a meningitis diagnosis from January 2021 to December 2022 will be eligible for the study. All meningitis survivors will be referred to the Ear, Nose and Throat (ENT)/audiology clinic prior to discharge for an ear and hearing assessment. The dependent variables will be otoscopic result and audiometry result for each ear. The independent variables will be age, gender, causal meningitis pathogen, and place of residence (urban/rural/remote). # Ethics and conclusions We publish this protocol to facilitate similar research studies, especially among our Pacific Island neighbours. This research protocol may be a useful resource for the development of clinical procedures for routine ENT/audiology assessments for patients following infection with known causes of hearing loss. This study was approved by the Government of Samoa Ministry of Health Ethical Research Committee and the University of Queensland Medical Ethics Research Committee.